2021
DOI: 10.1177/1708538120988418
|View full text |Cite
|
Sign up to set email alerts
|

Extended thoracic endovascular aortic repair for residual aortic dissection after type A aortic dissection repair

Abstract: Objective We investigated the outcomes of extended coverage of the descending thoracic aorta by thoracic endovascular aortic repair (TEVAR) for residual chronic type B aortic dissection after type A aortic dissection (TAAD) repair. Methods From November 2015 to August 2020, 36 patients underwent extended TEVAR for residual intimal tear after TAAD repair. We specifically investigated the methods and outcomes of this procedure. Results TEVAR consisted of isolated TEVARs ( n = 29), single-vessel debranching TEVAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In their study, Iida et al examined the conditions and consequences of TEVAR procedure performed for residual aortic dissection after TAAD [19]. They showed that after total arch surgery and elephant trunk procedure in the first operation of 52.8% of the patients, >55-60mm distal aortic diameter, >5mm aortic diameter enlargement in 6 months, postoperative true lumen stenosis and intimal tear in the descending thoracic aorta were the cause of reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Iida et al examined the conditions and consequences of TEVAR procedure performed for residual aortic dissection after TAAD [19]. They showed that after total arch surgery and elephant trunk procedure in the first operation of 52.8% of the patients, >55-60mm distal aortic diameter, >5mm aortic diameter enlargement in 6 months, postoperative true lumen stenosis and intimal tear in the descending thoracic aorta were the cause of reintervention.…”
Section: Discussionmentioning
confidence: 99%